Regiocontrolled Ring Opening of Monoprotected 2,3-Epoxy-1,4-diols by Using Alkynyl Aluminum Reagents: Synthesis of Differentially Monoprotected Alkynyl Triol Derivatives - Prieto, José A.; Torres, Jaileen Rentas; Rodríguez-Berrios, Raul (Synlett, 2014)
The regioselectivity of the epoxide ring-opening reaction of cis and trans TIPS-monoprotected 2,3-epoxy-1,4-diols with diethylalkynyl aluminum reagents was studied. Alane and alanate conditions in toluene or dichloromethane were explored. Alkynyl attack at the C2 epoxide carbon was favored under both the alane and alanate conditions in toluene, whereas C3 attack was preferred in dichloromethane. The best regioselectivities were obtained by using the alanate conditions in toluene. This methodology provides access to differentially monoprotected alkynyl triols with high diastereoselectivity. These compounds are useful building blocks for polypropionate synthesis and are precursors for the introduction of the hydroxymethyl moiety found in some polyketide systems.
Keywords: epoxide cleavage; epoxy alcohols; alkynes; regioselectivity; diastereoselectivity